"Yetzer" anthropologies in the "Apocalypse of Abraham" - Orlov, Andrei A. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Cover -- Title -- Contents -- Preface -- Abbreviations -- Introduction -- Chapter One: Yetzer Terminology in the Apocalypse of Abraham -- 1.1 Methodological Difficulties -- 1.1.1 Terminological Uncertainties -- 1.1.2 Conceptual Ambiguities -- 1.1.3 Translational Challenges -- 1.2 Terminology of "Heart" -- 1.3 Terminology of "Desire" -- 1.4 Terminology of "Thought" -- 1.5 Terminology of "Counsel" -- Chapter Two: Yetzer Traditions in the Haggadic Section -- 2.1 Idolatry and Yetzer -- 2.2 Human Heart and Yetzer in Abraham's Story in the Book of Jubilees -- 2.3 Protological Traditions in the Haggadic Section -- Chapter Three: Yetzer Traditions in the Apocalyptic Section -- 3.1 Reification of Yetzer -- 3.1.1 Two Ways Traditions -- 3.1.2 Two Lots Traditions -- 3.1.3 Internalization of Evil in Early Enochic Materials -- 3.1.4 Internalization of Evil in the Book of Jubilees -- 3.1.5 Internalization of Evil in the Qumran Materials -- 3.1.6 Demonological Developments in the Apocalypse of Abraham -- 3.1.7 The Antagonist's Control over the Human Race: Azazel's Lot -- 3.1.8 Azazel's Will: Backdoor to the Human Nature? -- 3.2 Sexualizing Yetzer: Azazel -- 3.2.1 Azazel as the Serpent and the Serpent as Yetzer Hara -- 3.2.2 Azazel as the Tree of Knowledge and the Tree of Knowledge as Yetzer Hara -- 3.3 Sexualizing Yetzer: Eve -- 3.4 Gendering Yetzer -- 3.5 Nationalizing Yetzer -- Chapter Four: Conquering the Evil Inclination -- 4.1 Adam, Azazel, and Abraham -- 4.2 Torah and Yetzer -- 4.3 Angelic Assistance -- 4.4 Exorcistic Tools -- Chapter Five: Anthropologies of Yetzer -- 5.1 Anthropologies of Yetzer in Rabbinic Accounts -- 5.2 Anthropologies of Yetzer in the Apocalypse of Abraham -- 5.2.1 "Biblical" Pattern -- 5.2.2 "Pseudepigraphical" Pattern -- 5.2.3 "Late Rabbinic" Pattern -- Conclusion -- Bibliography -- Index of Sources -- Index of Authors.